Sustainable waste management solutions: Optimization of hybrid and gasification waste-to-energy plants - Gonçalves Mollica, Gustavo José [UNESP]; Cerda Balcazar, Juan Galvarino; Alves Dias, Rubens [UNESP]; Perrella Balestieri, José Antônio [UNESP] (Elsevier, 2024)
This study investigates an urban waste management model to integrate different energy generation technologies and waste processing routes in a megastructure with thermal, biological, and recyclable superstructures. The model was simulated for three metropolitan regions in Brazil, with waste transportation between existing landfills to improve energy generation efficiency and financial income. The gasification appears as a promising alternative to the originally modeled hybrid incineration configuration. Results suggest that the overall financial performance of plants benefits when the utilization of the thermal superstructure is restricted in smaller plants, with waste mass flow of less than 6 kg/s. Gasification is preferred for bigger plants, with paybacks of up to 11 years, net present value of 2 billion dollars, and an internal rate of return of 20.32 % in the most likely scenario without subsidies. The study shows significant increase in attractiveness by the utilization of waste-collecting taxes, for which a payback of 6 years was reached, demonstrating it as a financially interesting. The internal rate of return results confirms the economic feasibility of the business for scenarios with waste-collection taxes. Integrating gasification technology in municipal waste management into the megastructure model emerges as a promising approach for sustainable waste management and energy generation.
Keywords: Decision-making process; Municipal solid wastes; Optimization; Processing technologies; Sustainability